Models of information search: A comparative analysis - Joseph, Pauline; Debowski, S.; Goldschmidt, P. (Professor T.D. Wilson, 2013)
Introduction. This paper describes how the seminal information seeking behaviour models of Ellis, Meho and Tibbo and Marchionini were used as scaffolds to examine the information search behaviour of users working with a commonly implemented information source in organizations: electronic document and record management systems. Method. A literature review on the information seeking behaviour models was conducted prior to hypothesising the search behaviour of electronic document and record management systems users. Ellis's, Meho and Tibbo's and Marchionini's models were identified as seminal frameworks to consider. A case study method was used to collect the data, using multiple research tools such as interviews, questionnaires and protocol analysis with forty users across four organizations and three different systems. Results. Transcripts of the interviews and protocol analysis of the search processes formed the data for analysis. From the protocol analysis, flow charts for each of the forty users' searches were plotted. Conclusions. The search results supported the hypothesised model and enabled identification of users' search behaviour; thereby contributing to an understanding of knowledge workers' context specific search behaviour.